Hybridity testing of eggplant F1 progenies derived from parents with varying responseto drought using SSR markers - Maravilla, Ana Mikaela B.; Ocampo, Eureka Teresa M.; Canama, Alma O.; Delfin, Evelyn F. (2017)
Eggplant (Solanum melongena L.) production is highly affected by drought stress, with effects including reduction in plant height, dry matter and fruit yield. However, some eggplant varieties were found to have tolerance to drought and can be used to confer drought tolerance to other varieties. Commercial eggplant varieties Mara and Mistisa were crossed with drought-tolerant eggplant accessions PHL 2789 and PHL 4841, respectively. To confirm that the F1 progenies indeed came from the cross made between the two selected parents, analysis was done at the molecular level using simple sequence repeat (SSR) markers. Out of 65 SSR markers screened for polymorphism, six markers (EM141, eme05B09, EM133, emh11O01, emf21I02 and EM117) were able to discriminate between Mistisa and PHL 4841 and four markers (CSM20, eme09E09, EM131 and EES063) were able to distinguish Mara from PHL 2789. These markers were used to determine the hybridity of the 30 progenies from each cross. Based on marker data, all progenies except for progeny number 13 were identified as hybrids for the cross Mistisa x PHL 4841 while all the 30 progenies from the cross Mara x PHL 2789 were confirmed as hybrids. (Author's abstract)